Opinions on hypertension care and therapy adherence at the healthcare provider and healthcare system level: a qualitative study in the Hague, Netherlands - Mattijs E Numans; Michiel L Bots; Sytske van Bruggen; Hedwig M M Vos; Rimke C Vos; Guy Rutten; Saskia E van Grondelle; Judith Meijer; Erik van Duin (BMJ Open)
Objectives Hypertension is a common cause of cardiovascular morbidity and mortality. Although hypertension can be effectively controlled by blood pressure-lowering drugs, uncontrolled blood pressure is common despite use of these medications. One explanation is therapy non-adherence. Therapy non-adherence can be addressed at the individual level, the level of the healthcare provider and at the healthcare system level. Since the latter two levels are often overlooked, we wished to explore facilitators and barriers on each of these levels in relation to hypertension care for people with hypertension, with a specific focus on therapy adherence.Design Qualitative study using focus groups of healthcare providers. Data were analysed using the theoretical domains framework (TDF) and the behaviour change wheel.Setting and participants Participants were from a highly urbanised city environment (the Hague, Netherlands), and included nine primary care physicians, six practice nurses and five secondary care physicians involved in hypertension care.Results Nine domains on the TDF were found to be relevant at the healthcare provider level (‘knowledge’, ‘physical, cognitive and interpersonal skills’, ‘memory, attention and decision processes’, ‘professional, social role and identity’, ‘optimism’, ‘beliefs about consequences’, ‘intention’, ‘emotion’ and ‘social influences’) and two domains (‘resources’ and ‘goals’) were found to be relevant at the system level. Facilitators for these domains were good interpersonal skills, paying attention to behavioural factors such as medication use, and the belief that treatment improves health outcomes. Barriers were related to time, interdisciplinary collaboration, technical and financial issues, availability of blood pressure devices and education of people with hypertension.Conclusions This study highlighted a need for better collaboration between primary and secondary care, for more team-based care including pharmacists and social workers, tools to improve interpersonal skills and more time for patient–healthcare provider communication.